New Organotin (IV) Compounds Derived from Dehydroacetic Acid and Thiosemicarbazides: Synthesis, Rational Design, Cytotoxic Evaluation, and Molecular Docking Simulation - Elizabeth Gómez; José Miguel Galván-Hidalgo; Guillermo Pérez-Cuéllar; Karoline Alondra Huerta-Landa; Arturo González-Hernández; Omar Gómez-García; Dulce Andrade-Pavón; Teresa Ramírez-Apan; Karla Daniela Rodríguez Hernández; Simón Hernández; Patricia Cano-Sánchez; Homero Gómez-Velasco (Bioinorganic Chemistry and Applications)
Organotin complexes were prepared through a one-pot reaction with three components by reacting thiosemicarbazide or 4-methyl-3-thiosemicarbazide or 4-phenylthiosemicarbazide, dehydroacetic acid (DHA) and dibutyl, diphenyl, dicyclohexyl, and bis[(trimethylsilyl)methyl]tin(IV) oxides; all complexes were characterized by infrared (IR), ultraviolet-visible (UV-vis), mass spectrometry (MS), and nuclear magnetic resonance (NMR) spectroscopy. The 119Sn NMR revealed chemical shifts corresponding to a pentacoordinated environment in solution. The X-ray crystallography of the two complexes evidenced the formation of monomeric complexes with a pentacoordinated geometry around tin via three donor atoms from the ligand, the sulfur of the thiol, the nitrogen of the imine group, and the oxygen of the pyran ring. The geometries of the five-coordinated complexes 3a (Bu2SnL3), 3c (Ph2SnL3), and 3d (Cy2SnL3) acid were intermediate between square pyramidal and trigonal bipyramidal, and complex 1a (Bu2SnL1) adopted a bipyramidal trigonal geometry (BPT). The sulforhodamine B assay assessed the cytotoxicity of organotin(IV) complexes against the MDA-MB-231 and MCF-7 (human mammary adenocarcinoma) cell lines and one normal COS-7 (African green monkey kidney fibroblast). The IC50 values evidenced a significant antiproliferative effect on cancer cells; the complexes were more potent than the positive cisplatin control and the corresponding ligands, dehydroacetic acid thiosemicarbazone (L1), dehydroacetic acid-N(4)-methylthiosemicarbazone (L2), and dehydroacetic acid-N(4)-phenylthiosemicarbazone (L3). The IC50 values also indicated that the organotin(IV) complexes were more cytotoxic against the triple-negative breast cell line MDA-MB-231 than MCF-7, inducing significant morphological alterations. The interactions of organotin(IV) 1c (Ph2SnL1), 1d (Cy2SnL1), and 1e (((CH3)3SiCH2)2SnL1) were evaluated with ss-DNA by fluorescence; intensity changes of the fluorescence were indicative of the displacement of ethidium bromide (EB), confirming the interaction of the organotin(IV) complexes with ss-DNA; the results showed a DNA binding affinity. The thermodynamic parameters obtained through isothermal titration calorimetry showed that the interaction of 1c (Ph2SnL1), with ss-ADN, was exothermic. Molecular docking studies also demonstrated that the organotin(IV) complexes were intercalated in DNA by conventional hydrogen bonds, carbon-hydrogen bonds, and π-alkyl interactions. These complexes furthermore showed a greater affinity towards DNA than cisplatin.